Independence square eaudiobook Arkady renko in ukraine. - Smith, Martin Cruz (Simon & Schuster Audio, 2023)
Detective Arkaday Renko—"one of the most compelling figures in modern fiction" ( USA TODAY )—risks his life when he heads to Ukraine shortly before the Russian invasion to find an anti-Putin activist who has mysteriously disappeared. Martin Cruz Smith has written nine previous novels featuring Arkady Renko, one of modern detective fiction's most popular characters. These novels, beginning with 1981's international sensation Gorky Park , have collectively traced Russia's evolution over the last half-century. Now, with Independence Square , Smith focuses on the fraught and frenzied days leading up to Vladimir Putin's war against Ukraine. It's June 2021, and Arkady knows that Russia is preparing to invade and subsequently annex Ukraine as it did Crimea in 2014. He is, however, preoccupied with other grievances. His longtime lover, Tatiana Petrovna, has deserted him for her work as an investigative reporter. His corrupt boss has relegated him to a desk job. And he is having trouble with his dexterity and balance. A visit to his doctor reveals that these are symptoms for Parkinson's Disease. This is an ingenious autobiographical conceit, as Martin Cruz Smith has Parkinson's, and is able through Arkady to movingly describe his own experience with the disease. Parkinson's hasn't stopped Smith from his work, and neither does it stop Arkady. Rather than dwell on his diagnosis, he throws himself into another case. An acquaintance has asked him to find his daughter, Karina, an anti-Putin activist who has disappeared. In the course of the investigation, Arkady falls for Karina's roommate, Elena, a Tatar from Ukraine. The search leads them to Kyiv, where rumblings of an armed conflict grow louder. Later, in Crimea, Tatiana reemerges to complicate Arkady's new romance. And as he gets closer to locating Karina, Arkady discovers something that threatens his life as well as the lives of both Elena and Tatiana. Few fiction writers have better captured contemporary Russia with more insight or authenticity than Martin Cruz Smith. He does the same here for Ukraine and the events that preceded Russia's invasion. Independence Square is a timely and a uniquely personal mystery novel-meets-political thriller by a master of the form.